2012
DOI: 10.1021/ja211874u
|View full text |Cite
|
Sign up to set email alerts
|

A Germanium Isocyanide Complex Featuring (n → π*) Back-Bonding and Its Conversion to a Hydride/Cyanide Product via C–H Bond Activation under Mild Conditions

Abstract: ABSTRACT:Reaction of the diarylgermylene, Ge(Ar Me 6) 2 (Ar Me 6 = C6H3-2,6-(C6H2-2,4,6-(CH3)3)2 with tertbutylisocyanide gave the Lewis adduct species, (Ar Me 6) 2GeCNBu t , in which the isocyanide ligand displays a decreased C-N stretching frequency consistent with an n -π* back-bonding interaction. Density functional theory confirms that the HOMO is a Ge-C bonding combination between the lone pair of electrons at the germanium atom and the C-N π* orbital of the isocyanide ligand. The complex undergoes facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 22 publications
8
55
0
Order By: Relevance
“…Klinkhammer already reported reactions of bis[tris(trimethylsilyl)silyl]stannylene and plumbylene with tert‐ butylisocyanide and cyclohexylisocyanide to form stable adducts . Additionally, Power and co‐workers described the conversion of tert‐ butylisocyanide with a diarylgermylene, which underwent a subsequent decomposition step that involved C−H activation of the tert ‐butyl group and formation of isobutene and a germylnitrile …”
Section: Resultsmentioning
confidence: 99%
“…Klinkhammer already reported reactions of bis[tris(trimethylsilyl)silyl]stannylene and plumbylene with tert‐ butylisocyanide and cyclohexylisocyanide to form stable adducts . Additionally, Power and co‐workers described the conversion of tert‐ butylisocyanide with a diarylgermylene, which underwent a subsequent decomposition step that involved C−H activation of the tert ‐butyl group and formation of isobutene and a germylnitrile …”
Section: Resultsmentioning
confidence: 99%
“…A signal at d = 139.2 ppm confirms the presence of a cyanide group. [14] In the IR spectrum of compound 2, a medium band at n = 2131 cm À1 further confirms the presence of the cyano group.…”
mentioning
confidence: 85%
“…22 Power et al reported the isolation and X-ray characterization of Ar 2 GeCN t Bu [Ar = C 6 H 3 -2,6-(C 6 H 2 -2,4,6-(CH 3 ) 3 ) 2 ], which was further converted to Ar 2 GeH(CN) and isobutene upon heating through heterolytic cleavage of the N t Bu bond. 23 Sekiguchi and Ichinohe reported the reaction of disilyne, RSi¸SiR (R = Si i Pr[CH(SiMe 3 ) 2 ] 2 ), with tert-butyl isocyanide to form a disilyneisocyanide adduct below ¹30°C. Warming the solution caused decomposition and produced 1,2-dicyanodisilene R(NC)Si=Si(CN)R and 1,2-dicyanodisilane R(NC)HSiSiH(CN)R together with isobutene and isobutane.…”
mentioning
confidence: 99%